Asymmetric Synthesis of α‐Amino Phosphonic Acids using Stable Imino Phosphonate as a Universal Precursor. Issue 60 (20th September 2019) - Inokuma, Tsubasa; Sakakibara, Takuya; Someno, Takatoshi; Masui, Kana; Shigenaga, Akira; Otaka, Akira; Yamada, Ken‐ichi
Abstract: A practical method for synthesizing chiral α‐amino phosphonic acid derivatives was developed. Readily available and stable N‐o ‐nitrophenylsulfenyl (Nps) imino phosphonate was utilized as a substrate for a highly enantioselective Friedel–Crafts‐type addition of indole or pyrrole nucleophiles catalyzed by chiral phosphoric acid. The resulting adduct was easily converted into N ‐9‐fluorenylmethyloxycarbonyl (Fmoc) amino phosphonic acid, which is useful for synthesizing peptides containing an amino phosphonic acid. Abstract : Stable imino phosphonate : Enantioselective Friedel–Crafts‐type reaction of imino phosphonate and indoles or pyrroles has been achieved (see scheme). The readily available and stable N ‐2‐nitrophenylsulfenyl (Nps) imino phosphonate can be used as a universal substrate, and the protective groups of the adducts (Nps and Bn) could be readily removed to generate biologically important α‐amino phosphonic acid derivatives.